2017
DOI: 10.1002/2017gl074886
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnection Between Atlantic Multidecadal Variability and European Temperature: Diversity and Evaluation of the Coupled Model Intercomparison Project Phase 5 Models

Abstract: A realistic simulation of the Atlantic Multidecadal Variability (AMV) and related teleconnections is essential to resolve and understand the potential predictability over Europe at decadal timescale. Based on a large ensemble of state-of-the-art climate models, we show that a considerable intermodel spread exists in the spatiotemporal properties of the simulated AMV and teleconnections with European summer temperature. The greater the persistence, variance, and basin-scale spatial coherence, the stronger the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 45 publications
4
62
0
Order By: Relevance
“…Furthermore, the sum of TNA and XNA experiments again yields similar anomalies to that of the full AMV experiment, but with a stronger magnitude. Therefore, this nonlinearity suggests that there are interference between the response to both TNA and XNA, as proposed in Qasmi et al (2017).…”
Section: Tropical Extratropical Warming and Linearity Of The Effectsmentioning
confidence: 84%
“…Furthermore, the sum of TNA and XNA experiments again yields similar anomalies to that of the full AMV experiment, but with a stronger magnitude. Therefore, this nonlinearity suggests that there are interference between the response to both TNA and XNA, as proposed in Qasmi et al (2017).…”
Section: Tropical Extratropical Warming and Linearity Of The Effectsmentioning
confidence: 84%
“…Bollasina et al 2011, Cui et al 2014, Guo et al 2015. Given the considerable uncertainties surrounding the methods used to disentangle the internal and externally forced variations in observations and historical simulations (Qasmi et al 2017), it remains unclear whether the positive AMO-ISM correlation observed during the industrial era is an inherent feature of the climate system, a response to external forcing, or an artifact of the relatively short observational record compared to the timescales of the AMO and ISM variability. Luo et al (2017) evaluated the AMO-ISM connections in 66 historical runs of 22 CMIP5 models, and found that most of the models have great difficulty in capturing the observed AMO-ISM connection; plus, there is a large spread between runs with the same model, except for GFDL-CM3 and HadGEM2-ES (figure S1 is available online at stacks.iop.org/ERL/ 13/094020/mmedia).…”
Section: Introductionmentioning
confidence: 99%
“…3) Ocean-land teleconnections. Motivated by the strong relationship at regional scales between observed oceanic DCV modes and land anomalies, emphasis should be placed on improved understanding of the ocean-land connection at low frequency, especially as CMIP5 models tend to underestimate the overall relationship [see Qasmi et al (2017) for the AMO] and decadal hindcast skill is critically reduced over the continents. The spatial imprint of the observed hiatus in the early 2000s (strong cooling over North America and Eurasia during wintertime as an important contributor to the slower rise in annual global temperature) as well as recent modeling studies highlight the importance of investigating these issues on a seasonal basis and in terms of changes in the entire probability density function of key parameters such as surface air temperature and precipitation (surmising that the ocean-land connection could occur through changes in the probability of extremes).…”
Section: ) Tropical-extratropical Teleconnectionsmentioning
confidence: 99%
“…This is perplexing in light of the findings that coupled models with SST restored to the observed anomalies over the Atlantic are able to display part of the ocean's influence on land climate. Part of the loss of predictability over land may be related to systematic errors in the simulation of the spatial structure and temporal properties of the AMO in free coupled models and/or the weak associated teleconnections that communicate ocean signals to the continents Qasmi et al 2017). Skill in a given prediction system might also depend on the model representation of processes or chain of events leading to AMO phenomena.…”
Section: Halle Ng E S An D Outstan Ding Questionsmentioning
confidence: 99%
See 1 more Smart Citation